Proceedings of the 6th Asia-Pacific Education and Science Conference, AECon 2020, 19-20 December 2020, Purwokerto, Indonesia 2021
DOI: 10.4108/eai.19-12-2020.2309182
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Padlet in Teaching and Learning of Writing Recount Text at Senior High School in Palu City

Abstract: Writing skill is one of the essential skill in English language skills that should be mastered by Senior High school students. Meanwhile, writing is perceived as one of the most challenging and less attractive skills to be learned. The application of Padlet as a learning media is an alternative strategy for motivating and promoting students to write. Therefore, this study attempted to provide transparent information of the integration technology in teaching and learning English writing skills, particularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Moreover, Jong and Tan's (2021) findings were inconsistent with the previous studies, as they realized that the benefits of Padlet were hindered by various obstacles, including students' lack of devices, stable internet, and digital literacy. In contrast, Mulyadi et al (2021) reported that students did not encounter any difficulty while using Padlet due to its simple accessibility.…”
Section: Teachers' Written Feedback and Technologymentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, Jong and Tan's (2021) findings were inconsistent with the previous studies, as they realized that the benefits of Padlet were hindered by various obstacles, including students' lack of devices, stable internet, and digital literacy. In contrast, Mulyadi et al (2021) reported that students did not encounter any difficulty while using Padlet due to its simple accessibility.…”
Section: Teachers' Written Feedback and Technologymentioning
confidence: 92%
“…In literature, Rashid et al (2019) found that using Padlet encouraged the students to check and edit punctuation and grammar errors, as well as the accuracy of their vocabulary, before posting online, as it would be reviewed by the teacher. Mulyadi et al (2021) and Silas (2022) comparably found that Padlet increased the students' confidence to write and submit their work due to its simplicity and the feasibility feature of anonymity, which reduced students' fear of being judged by the teacher or friends. Padlet is a real-time participatory technology and hence the study focuses on how it provides the students equal chances to share their ideas and allows teachers to 'hear' all students' views.…”
Section: Padlet and Its Pedagogical Usementioning
confidence: 99%
See 1 more Smart Citation
“…First of all, Padlet encourages collaborative learning in class, particularly in writing and speaking. According to Mulyadi et al (2021), writing assignments is considered easier for both teachers and students, as they can post their products directly to the wall, and other classmates are likely to leave comments or feedback. By this method, students could learn from each other without feeling reluctant to be exposed to the whole class.…”
Section: Padlet Applicationmentioning
confidence: 99%
“…For example, the usage of Padlet as a platform for the educators and learners to be engaged, particularly during class sessions are resulting in a positive outcome with the learners' participation in the lesson. Based on the findings obtained from a study conducted by Mulyadi, Naniwarsih, Omolu, Manangkari, and Amiati (2021), the findings show that with the help of Padlet, students were enthused about and active in classroom activities. For decades, the traditional technique of teaching, which includes lectures and handouts, has been the usual way of instruction, and it was still being used in ESL classrooms.…”
Section: Introductionmentioning
confidence: 99%